MOTIVATION TO VISIT THE TOURIST ATTRACTION MEDUYAN LAKE INDRAGIRI HULU REGENCY - Larasati, Arum Dwi; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research using descriptive quantitative research method, there is a purpose to analyze problem in a Tourist Attraction Meduyan Lake Indragiri Hulu Regency. In addition, to find out the motivation to visit the tourist attraction Meduyan lake.The sample of data collection techniques on this research the writer using liker scale as an instrument to measuring the length of intervals that can be used to find quantitative data. The sample of this research was 100 respondent taken by using accidental sampling. Based on the research are the influence of the phusical motivation get 1.274 with scores with a very high category, fantasy motivation get 1.227 scores with a very high category, social motivation get 1.140 scores with a high category, and cultural motivation get 759 scores with a high category. Keyword: Motivation, Danau Meduyan, Visit